The Relationship between the level of anxiety of pregnant women and visits to antenatal care services during the Covid-19 pandemic at Puskesmas Bojong Rawalumbu Bekasi - Rotua Suriany Simamora; Farida M Simanjuntak; Riyen Sari Manullang (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. The spread and transmission of the SARS-CoV-2 virus was so fast that it was designated a COVID-19 pandemic. The pandemic requires the government to issue several rules to suppress the spread of the virus and this has an impact on everyone's psychology without exception for pregnant, postpartum and breastfeeding women. The coronavirus has disrupted pregnancy plans and heightened the anxiety of most expectant mothers, who question how the virus will affect the birth of their babies. Most pregnant women feel anxious about giving birth without their loved ones by their side. Others are afraid of being infected with COVID-19 and not being able to hug their baby. The coronavirus pandemic has added anxiety and uncertainty to the dire situation. This study is an observational analytic epidemiological study using a cross sectional design. The population in this study was 150 respondents where the sample was taken using quota sampling. Furthermore, bivariate analysis was performed using Chi Square. The results showed that the level of anxiety was related to antenatal care service visits during the COVID-19 pandemic with a p value of 0.001 and an Odds Ratio of 3.75.